Strategies of Student Youth’s Self-Representations in Choosing Behavioral Tendencies - Hrys , Antonina; Pavliuk , Oksana; Hoi , Nataliia; Los , Oksana (Insight: the psychological dimensions of society, 2024)
The aim is theoretical-empirical research of the dominant strategies of student youth’s self-presentations in the context of social desirability and actual behavioral tendencies. Methods. The sample involved students from three levels of higher education institutions of Ukraine representing socionomic and technonomic profiles and numbered n = 142 participants. The respondents’ age ranged from 18 to 28 years (M = 23.36; Me = 23.50; SD = ± 6.12). Theoretical and empirical research methods were used. Theoretical methods included analysis, synthesis and generalization. Empirical methods comprised a complex of valid and reliable methods which ensured determination of the parameters of self-representation, social desirability and behavioral tendencies. Standard methods of mathematical statistics were applied to establish statistically significant correlations and differences. Results and discussion. We registered eleven statistically significant correlations of self-representation strategies with the researched parameters, all of them being direct at the level р≤.050; р≤.010 and р≤.001. It was found that the assertive self-presentation strategy “Wanting to be liked” (AWL) (n = 102; 71.83%; М = 4.03; SD = ±.67) is dominant in student youth. We revealed the dual nature of student youth’s self-representation strategies and found that the dominant approval motivation manifests itself in constructive and destructive forms. It was established and explained that high social desirability with the behavioral tendency for dependence has a negative impact on intellectual and physical activities of adolescents. We warn that such a combination can be transformed into respondents’ psychological dependence on permanent self-approval, updating profiles in social networks and the desire to meet social expectations. Conclusions. We highlighted the danger which can be posed by high levels of the formedness of social desirability by the scales “self-deceit” and “managing impressions” for the formation of a young individual, if no prevention measures are taken to develop assertive self-presentation strategies. The findings of the applied research should be implemented in educational process, used in psychological theory and practice. The obtained scientific facts possess novelty and value for everyone working with student youth.
Keywords: social desirability, self-deceit, managing impressions, dependent behavior, sociability, communication, higher education institution, self-actualization.